2021
DOI: 10.1080/08870446.2021.1952586
|View full text |Cite
|
Sign up to set email alerts
|

Categorical interoception: the role of disease context and individual differences in habitual symptom reporting

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Furthermore, the discrimination of stimuli is more accentuated between than within these categories (31). It was furthermore indicated that a category's threat relevance (i.e., its ability to predict electric shock) and meaning (i.e., being arbitrary versus discriminating symptoms from benign sensations) further impacts interoception (30,32). Classification choice behavior (e.g., assigning stimuli to a category of low or high intensity), however, remained largely unaffected in these studies investigating nonclinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the discrimination of stimuli is more accentuated between than within these categories (31). It was furthermore indicated that a category's threat relevance (i.e., its ability to predict electric shock) and meaning (i.e., being arbitrary versus discriminating symptoms from benign sensations) further impacts interoception (30,32). Classification choice behavior (e.g., assigning stimuli to a category of low or high intensity), however, remained largely unaffected in these studies investigating nonclinical samples.…”
Section: Introductionmentioning
confidence: 99%